2006
DOI: 10.1200/jco.2006.05.6861
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic Predictor of Sensitivity to Preoperative Chemotherapy With Paclitaxel and Fluorouracil, Doxorubicin, and Cyclophosphamide in Breast Cancer

Abstract: A 30-probe set pharmacogenomic predictor predicted pCR to T/FAC chemotherapy with high sensitivity and negative predictive value. This test correctly identified all but one of the patients who achieved pCR (12 of 13 patients) and all but one of those who were predicted to have residual disease had residual cancer (27 of 28 patients).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
568
0
16

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 620 publications
(600 citation statements)
references
References 22 publications
(7 reference statements)
11
568
0
16
Order By: Relevance
“…Conversely, FNA can collect a small sample size, approximately 30% of samples reportedly are not evaluable, and the success rate reported by Hess et al was approximately 70%. 12 However, those authors used the oligo-dT method for RNA amplification, which requires a larger amount of RNA than the random primer method that we used in the current study. Thus, the success rates of the 2 biopsy methods cannot be compared because of the different protocols for RNA amplification.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Conversely, FNA can collect a small sample size, approximately 30% of samples reportedly are not evaluable, and the success rate reported by Hess et al was approximately 70%. 12 However, those authors used the oligo-dT method for RNA amplification, which requires a larger amount of RNA than the random primer method that we used in the current study. Thus, the success rates of the 2 biopsy methods cannot be compared because of the different protocols for RNA amplification.…”
Section: Discussionmentioning
confidence: 97%
“…Hess et al 12 reported that 31-gene classifier analysis using FNA samples was useful for predicting the response to P-FAC. The NPV (96%) and PPV (52%) of that 31-gene classifier were very similar to those obtained with the 70-gene classifier in our study using core-needle samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations